Digital networking boosts financial prospects for women agripreneurs - Bafana, Busani; Hosenally, Nawsheen (Technical Centre for Agricultural and Rural Cooperation, 2019)
It might keep the world fed, but there is little appetite for financing farming and farmers. Women in farming count access to finance as top of their challenges. Many run informal businesses. Expanding them into large operations comes with a long list of demands, including access to funding, collateral, business skills and a record of farming accomplishment. Digital technologies can help to boost prospects for women agripreneurs.